Local wisdom-based management in MSME HR Management: A Case Study of Siri' na Pacce value in Makassar - Burhanuddin, Burhanuddin (Abadi Institute, 2025)
This study explores how the indigenous values of Siri’ (dignity, honor) and Pacce (compassion, shared feeling) shape human resource management (HRM) practices among micro, small, and medium enterprises (MSMEs) in Makassar, Indonesia. Using a qualitative case study design, the research examines leadership as a cultural-economic institution in which moral commitments guide organizational behavior, employee motivation, and firm resilience. Data were collected through semi-structured interviews, participant observation, and document analysis involving ten MSME leaders in the trade, culinary, and craft sectors. Thematic analysis revealed that Siri’ informed dignity-preserving disciplinary practices and accountability norms, while Pacce manifested through mutual aid systems and empathetic management. Decision-making was consensus-oriented, integrating hierarchical authority with community deliberation. These practices produced positive HRM outcomes such as job satisfaction, loyalty, and ethical reputation, yet also imposed financial and emotional strains due to the moral obligation to preserve collective welfare. The findings suggest that Siri’ na Pacce-based leadership functions as a moral economy that substitutes social capital and emotional intelligence for formal control systems. This culturally grounded model enhances organizational legitimacy and sustainability but requires careful balancing between moral duty and economic pragmatism. The study contributes to humanist economic theory by demonstrating how local wisdom can inform dignity-centered, relational HRM systems in developing contexts.